"The Action to the Word, the Word to the Action": reading hamlet with cavell and derrida. Issue 2 (2nd April 2016) - Rudrum, David; Lodge, April; Christofides, R.M.
Abstract: The writings of Stanley Cavell and Jacques Derrida share many points of intersection. One of these is their mutual interest in Shakespeare's Hamlet ; another is their (very different) assessments of J.L. Austin's philosophy, and his concept of performativity. In this paper, we demonstrate that Cavell's and Derrida's respective essays on Hamlet offer a surprising insight into their views on Austin's notion of performativity. Since Hamlet abounds with oaths and promises, testimonies and bearing witness, what is surprising is not that these philosophers should have identified this theme but rather how they respond to it. We show that Derrida's writings on Hamlet repeatedly draw and depend on the idea of performativity, amounting to a rapprochement with Austin's concept; and we also show that Cavell questions the effectiveness of performatives in the play, in ways that sometimes resemble Derrida's invocation of spectrality in the play.